Strategi Promosi Universitas Bina Darma - Dian Rianawati (MBIA, 2022)
The purpose of this study was to determine the factors that caused the decline in new students in the sports education study program at Bina Darma University. The research method used in this study was a qualitative method. After conducting research and discussing cases that caused a decrease in the number of new students in the sports education study program, the results showed that the most dominant factor causing the sports education study program was not popular for students who would continue to college. The cost factor was also a consideration because the majority students of the sports education study program come from the regions and have income from farming and teachers. Efforts are being made to increase new students of the sports education study program by carrying out more aggressive promotions (Growth Oriented Strategy) among others by increasing the intensity of promotions for Sports Education study program with a concentration in the target market segment., strategies for using alumni as facilitators in promoting, Word Of Mouth so that promotional activities are effective and efficient and on target. Keywords: New Students, Growth Oriented Strategy , Word Of Moutht Abstrak Tujuan penelitian ini adalah untuk mengetahui faktor yang penyebab turunnya mahasiswa baru pada program studi pendidikan olahraga di Universitas Bina Darma. Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif. Setelah melakukan penelitian dan pembahasan kasus yang menyebabkan turunnya jumlah mahasiswa baru pada program studi pendidikan olahraga diperoleh hasil bahwa faktor yang paling dominan yang menyebabkan adalah karena program studi pendidikan olahraga tidak populer bagi siswa yang akan melanjutkan ke perguruan tinggi. Faktor biaya juga menjadi pertimbangan disebabkan mayoritas mahasiswa program studi pendidikan olahraga berasal dari daerah dan dan memiliki penghasilan dari bertani dan guru .Upaya yang dilakukan untuk meningkatkan mahasiswa baru program studi pendidikan olahraga dengan melakukan promosi yang lebih agresif (Growth Oriented Strategy ) antara lain dengan meningkatkan ;Intensitas promosi yang lebih banyak untuk program studi Pendidikan Olahraga dengan konsentrasi di segmen pasar yang menjadi target.,strategi pemanfaatan alumni sebagai fasilitator dalam mempromosikan, Word Of Mouth sehingga kegiatan promosi efektif dan efisien serta tepat sasaran. Kata kunci: Mahasiswa baru, Growth Oriented Strategy , Word Of Moutht